Református női sors és nőkérdés a 20. század első felében. II. rész. Victor Gabriella női vonatkozású művei - ACKERMANNÉ KELŐ, Kamilla (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
Calvinist Women’s Fate and Women’s Issues in the First Half of the 20th Century. Part II. Victor Gabriella’s studies and literary works related to women The purpose of the research is to present the scientific and religious foundations of Gabriella Victor’s pedagogy. The name of the Victor family is inseparable from the cause of the reformist revival and the internal mission. Gabriella Victor (1891–1971) is the first teacher of the Reformed Teacher Training School in Kecskemét, Head of Lórántffy Zsuzsanna Association. She published a number of articles, children’s Bible, juvenile novels, and informative books for parents and teachers alike. She was the Doctor of Philosophy (1917) and Theology (1950). The main topics of her scientific work are women’s education, Christian family education, and school religious education. In this study, we present the activities of the Victor family in the internal mission, Gabriella Victor’s opinion on women’s issues, and her views on the characteristics of the female psyche.